Faktor-Faktor yang Berhubungan dengan Peran Bidan dalam Pemantauan dan Deteksi Dini Resiko Tinggi Kehamilan - Danur Azissah; Dwi Wulandari (Jurnal Keperawatan Silampari, 2018)
The purpose of this study was to determine the factors associated with the role of midwives in monitoring and early detection of high risk of pregnancy in the work area of Basuki Rahmat Health Center. The research method uses quantitative research with cross sectional study approach. The results of the study, more 60% of respondents had an unfavorable midwife role, 52% were early adulthood, 16% had low education, 48% had sufficient knowledge, 55% had a favorable attitude, 60% had high motivation, 44% had never had training , 60% never get rewards, 40% never get supervision. Conclusion, there is no significant relationship between education and the role of midwives in monitoring and early detection of high risk of pregnancy. Keywords: Early Detection, Monitoring, Role of Midwives